ANALYSIS OF OWNERSHIP STRUCTURE INFLUENCE ON COMPANY VALUE IN THE PROPERTY AND REAL ESTATE INDUSTRY ON THE INDONESIA STOCK EXCHANGE - Akbar, Muhammad; Muslimin, Muslimin; Kasim, Muhammad Yunus (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims at determining the influence of ownership structure on company value of property and real estate industry on the Indonesia Stock Exchange. This research was quantitative research using panel data regression analysis. The object of this research was property and real estate companies listed on Indonesia Stock Exchange in 2010-2019. The results indicate that the ownership structure consisting of managerial ownership, institutional ownership, and foreign ownership together have a significant influence on company value. Managerial ownership partially has no effect on company value. Partial institutional ownership has a significant negative influence on company value. Partial foreign ownership has no influence on company value. Keywords: Managerial Ownership, Institutional Ownership, Foreign Ownership, Company Value.